Accumulation of the advanced glycation end product carboxymethyl lysine in breast cancer is positively associated with estrogen receptor expression and unfavorable prognosis in estrogen receptor-negative cases - Naß, Norbert; Sel, Saadettin (Histochemistry and cell biology, 2017)
Advanced glycation end products (AGEs) accumulate as a result of high concentrations of reactive aldehydes, oxidative stress, and insufficient degradation of glycated proteins. AGEs are therefore accepted biomarkers for aging, diabetes, and several degenerative diseases. Due to the Warburg effect and increased oxidative stress, cancer cells frequently accumulate significant amounts of AGEs. As the accumulation of AGEs may reflect the metabolic state and receptor signaling, we evaluated the potential prognostic and predictive value of this biomarker. We used immunohistochemistry to determine the AGE Nε-carboxymethyl lysine (CML) in 213 mammary carcinoma samples and Western blotting to detect AGEs in cell cultures. Whereas no significant correlation between hormone receptor status and CML was observed in cell lines, CML accumulation in tumors was positively correlated with the presence of estrogen receptor alpha, the postmenopausal state, and age. A negative correlation was found for grade III carcinomas and triple-negative cases. In a retrospective Kaplan-Meier survival analysis, there was a statistical trend that high CML accumulation correlated with a more favorable prognosis (relapse-free survival, RFS) under tamoxifen treatment (p = 0.1). In estrogen receptor-negative cases, the high CML content was significantly correlated with an unfavorable outcome (RFS) of chemotherapy (p = 0.046). CML is a therefore a potentially predictive marker for the treatment of breast cancer patients with tamoxifen or chemotherapy.